Morphometric characteristics of acute swelling and induration of neurons in the critical zone of ischemic brain infarction - T. V. Shulyatnikova (Patologìâ)
This work presents the results of computer-morphometric study of brain neurons in perifocal critical zones of brain ischemic infarction in patients who died with clinically progressing and temporarily stabilized neurological symptoms. It is revealed that the critical zones of progressing cerebral infarction are characterized by more pronounced processes of neuronal swelling. On the contrary, the critical zones of clinically stabilized infarction show the prevalence and low variability of severity of neuronal induration processes.